ATLANTIS IN SPAIN III - Papamarinopoulos, S.P (Bulletin of the Geological Society of Greece, 2010)
Plato three times in his text mentioned that the Atlantean events occurred 9000 years before Solon’s 6th century B.C. but once he also mentioned 8000 years for the same events. Taking into account the number of the Athenian Kings and the mean span of their successive generations which is more or less 30 years who governed Athens before the 12th century B.C., it is concluded that all of them together span a 350 year period which of course has nothing to do with the 10th millennium claimed by Plato. These Kings together with Theseus the first King of Athens correspond in the 2ed millennium B.C. The archaeological findings in the Acropolis mentioned by Plato, the collapse of the Achaean World, the loss of the writing system in Greece, the assault of the Atlantes have been proved to be of the 12th century B.C. The ancient sources and the archaeological findings in Egypt show a lunar calendrical system practised by the priests who transmitted the story of Atlantis to Solon in the 6th century B.C. Dividing therefore these thousands of years by 12.37 which is the number of the full moon in a year the platonic dates are landing in the end of the 13th to the beginning of the 12th century B.C. Considering the visibility from Atlantis of the celestial bears which are implied as general North indicators Plato himself invalidated the 10th millennium B.C., as the period of the Atlantean events, since no celestial bears can play such a role as celestial North’s constellation because the Earth’s axis of rotation does not pass through them. This conclusion forces a different interpretation in Plato’s thousands of years for the Atlantean events. The only logical explanation is that the thousands of years is moon months understood as years. Plato used the word island for Atlantis which is associated with events belonging in the late Bronze Age in which the word island had the meaning of either promontory or peninsula. The resolution of this major issue removed entirely the 2400 year misunderstanding between the word island and peninsula since Herodotus in the 5th century B.C. added the word peninsula for first time offering to the island today’s exclusive meaning. In other words Atlantis was as much an island as Peloponnesus was which an island was never. He also used with the common word Atlantis three different geological entities: a giant island, a horseshow basin and a system of concentric rings associated with geothermal springs and with black, white and red rocks.